Handbook of population and family economics - Arrow, Kenneth J (Ed.); Intriligator, Michael D (Ed.) (Amsterdam Elsevier, 1997)
Handbook of population and family economics is in two volumes.The vol.1A contents are-The family,fertility,mortality and health.and vol.2B.contents are-Migartion aging,demographic composition and aggregate population change and economic growth etc.
Keywords: Economics-Handbooks, manuals, etc; Population-Economic aspects